Media Diaspora Pelajar Indonesia: Eksistensi, Peran, dan Spirit Keindonesiaan - Widodo, Yohanes (FISIP Universitas Atma Jaya Yogyakarta, 2017)
This paper discusses how Indonesian student diaspora has interacted with their peers and built their identity through media by looking at the role of Indonesian student diaspora media since pre-independence era to reform era (1900-2016). This paper found that Indonesian student diaspora media have existed since pre-independence to reform era. Each had its peculiarities in terms of type and role of media influenced by the dynamics and socio-political developments in Indonesia.